الوصف في شعر ملوك وقادة في الأندلس بين النّعمة والنقمة (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
الوصف من أهّم مقوّمات الشّعر وركائزه لحضوره في الأغراض الشعريّة كافّة، وهو يصوّر واقع الشعر العربي، ولا يقف عند رسم الأشكال، بل يعلّل وجودها، ويقاس بمعايير الجمال والدقّة، والقدرة على الإيحاء والتّصوير والبحث أمام الخيال، وقد أكثر الشّعراء الملوك والقادة من رسم الصور المتلاحقة لموصوفاتهم التّي استمدّوها من البيئة، فوصفوا ما حولهم من مظاهر الطبيعة والكون، فكان الوصف مظهراً من مظاهر التعلّق بالوطن والاعتزاز بطبيعته الغنّاء، وإقباله على مباهج الحياة، وتصويراً لمشاعرهم وتجربتهم القاسية التي عاينوها داخل السّجن، بما فيها من ملامح وخلجات ومواقف جديرة بالاهتمام والتّتبّع. وتتقصّى هذه الدراسة أشعار الملوك والقادة التي أُنشدت في الوصف، فمنها موصوفات أطالوا الوقوف عندها، ونالت من اهتمامهم الحظ الوافر، ونظموا فيها القصائد الطوال، كمظاهر الطبيعة الصامتة التي شكّلت موضوعاً من المواضيع المحبّبة إلى نفوسهم، تحفّزهم على النّظم فيه بطلاقة وتلقائيّة، طبيعة الأندلس الغنّاء، ونفسيّة الأندلسيّ الرقيقة التوّاقة إلى تجليّات الجمال، وصنف آخر من الموصوفات اكتفوا فيه بالوقفة العابرة واللمحة الخاطفة. وفي الجانب الآخر سنقف على تصوير تجربتهم في ظلام السجن بما فيها من مظاهر قهر وعذاب، ومشاهد فراق وحرمان، ونتتبع ملامح الصورة العامة للسجن من خلال معالجتنا للصور الجزئيّة التي رسمها كل شاعر في مواقف مختلفة. Description is one of the most important elements of poems and poetry, because of its presence in all poetic purposes. It depicts the reality of Arab poetry and is not limited to drawing shapes, but it accounts for their existence. It is measured by the standards of beauty and precision, and the ability to suggest, depict and search in imagination. Poet kings and leaders are abundant in giving consecutive images of the description subjects. Those images, or depictions, are taken from the environment, so they described manifestations of nature and the universe around them. Therefore, the description came as a manifestation of their passion for the homeland, and pride in the beautiful nature. It also came as an embracing of the joys of life, and as a depiction of their feelings and the harsh experience they have suffered inside the prison, including the features, the feelings and attitudes worthy of attention. This study investigates the poems of kings and leaders which were descriptive. Some of them are elongated descriptions where they composed long descriptive poems, such as those on the manifestations of silent nature, a subject endearing to them. It was so because this subject motivated them to spontaneously and fluently compose poems on the bright nature of Andalusia, and the tender personality of the Andalusian which was eager to the manifestations of beauty. On the other hand, there was another kind of description, which was swift and suggestive. On a different scale, we will portray in detail their experience in the darkness of the prison. We will follow the features of the general image of the prison, through our treatment of partial images drawn by each individual poet in different positions.